Control de emisiones de olores ofensivos en el sector pecuario: una revisión sistemática (2023)
Offensive odors emissions from livestock farms can cause nuisance and health effects to the persons who live in the area of influence of the facilities. With the purpose to reduce this conflict is necessary that farms implement good practices and technologies which allow them to reduce or eliminate offensive odors. In the present work, a bibliometric analysis was done to identify the trends in the area of offensive odors control in livestock farms. Scopus database was used to do the bibliometric search and VOSviewer © (version 1.6.18) software was used to do a co-occurrence analysis. As a result of the search strategy, 518 documents published between the years 2012 and 2022 were found. The keyword analysis reveals that the main livestock activities are swine, poultry and cattle raising. Further, the most researched technologies to control, mitigate and reduce unpleasant odors are anaerobic digestion, biofiltration, biotrickling, biochar adsorption and advanced oxidation processes. It is worth noting, that research applied in this productive sector indicates that these technologies are effective in reducing odor emissions and odorant substances such as NH3 and H2S.